Szkoła elementarna w Załęczu Wielkim (pow. wieluński) 1804–1859 - Włodarczyk, Zdzisław (Zeszyty Wiejskie, 2019)
The village of Załęcze Wielkie, located in the south-eastern part of the Wieluń district, was one of the villages of Kamionkowo dominium, which belonged to the chapter of the Gniezno archbishopric. As a result of the Second Partition of Poland, these areas came under the rule of the Hohenzollerns (1793), in the so-called South Prussia (Südpreussen). After the Kościuszko Uprising (1794), it was decided to confiscate them and create domains. The beginnings of elementary school in Załęcze Wielkie should be linked with the activities of the Prussian administration aimed at creating a network of schools in newly gained areas. The school probably started its activity in 1804 – when the school building was put into use. Throughout its existence, the facility struggled with material difficulties. The contribution of the village inhabitants was barely enough for the teacher’s salary. There was a lack of funds for proper maintenance of the school building. Hence the staffing trouble: teachers, especially in the last period of the school’s existence, changed very often. The facility existed until 1859, when it was closed by the decision of the educational authorities of the Kingdom of Poland.